Balanced Score Card: Transparency and Accountability of the Social Family's Hope Program (PKH) - Muhammad Rifqi H; Hilmi Hermawan; Siti Khumayah; Rahmayanti Rahmayanti (Publikasi Indonesia, 2025)
This study aims to analyze the level of transparency and accountability in the implementation of the Social Family's Hope Program (PKH) in Tukmudal Village, Cirebon Regency, using the Balanced Scorecard (BSC) approach developed by Kaplan and Norton. This approach was chosen because it provides a comprehensive overview of program performance, not only from a financial perspective but also from the perspectives of customers, internal business processes, and learning and growth. The method used is descriptive qualitative, with data collection techniques including in-depth interviews, field observations, and document studies. Data validity was tested using source triangulation. The research findings indicate that the implementation of the PKH program has been transparent and accountable, with targeted distribution of assistance funds and active participation from village officials, social workers, and the community. However, the long-term effectiveness of the program still needs to be strengthened through integration with economic empowerment programs. Thus, the implementation of the Balanced Scorecard can serve as an effective evaluation tool to improve the governance of social assistance programs, particularly in ensuring the sustainability of benefits for recipient families.